Service triads: A research agenda for buyer–supplier–customer triads in business services. Issue 1 (16th October 2014) - Wynstra, Finn; Spring, Martin; Schoenherr, Tobias
Abstract: Service triads, in which a buyer contracts with a supplier to deliver services directly to the buyer's customer, represent an emerging business model. This special issue is dedicated to this theme. To set the context, in this lead article, we first define service triads, both as a phenomenon and a research topic. We then provide a review of different strands of existing research and various theoretical frameworks that can inform our study of service triads. This culminates in an outline of a research agenda that can guide future study. As such, this paper not only introduces the articles in the special issue, but is also intended as a point of reference and motivation for further work on service triads, and on triads in general.